2015
DOI: 10.1101/025916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain Transcriptional Profiles of Male Alternative Reproductive Tactics and Females in Bluegill Sunfish

Abstract: Bluegill sunfish (Lepomis macrochirus) are one of the classic systems for studying male alternative reproductive tactics (ARTs) in teleost fishes. In this species, there are two distinct life histories: parental and cuckolder, encompassing three reproductive tactics, parental, satellite, and sneaker. The parental life history is fixed, whereas individuals who enter the cuckolder life history transition from sneaker to satellite tactic as they grow. For this study, we used RNAseq to characterize the brain trans… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 92 publications
2
13
0
Order By: Relevance
“…We found that each peacock blenny phenotype has a distinct transcriptomic profile (Figure a), indicating that distinct behavioural repertoires are associated with distinct neurogenomic states, which differentiate not only sex but also male morphs. These results are consistent with previous studies that have already described this parallel between specific behavioural states and neurogenomic states at different timescales (reviewed in Zayed & Robinson, ; Harris & Hofmann, ; Cardoso, Teles, & Oliveira, ), and with previous reports of specific brain transcriptomic profiles among species with ARTs for alternative male morphs, particularly in teleost fishes (Aubin‐Horth et al., ; Fraser et al., ; Nugent et al., ; Partridge et al., ; Schunter et al., ; Stiver et al., ). For example, in bluegill sunfish ( Lepomis macrochirus ), the three male ARTs, encompassing two distinct life histories, presented distinct neurogenomic profiles, with sneaker males having the most divergent expression profile, while parental males were further discriminated in the analysis relatively to their reproductive state (i.e., spawning vs. nonspawning; Partridge et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found that each peacock blenny phenotype has a distinct transcriptomic profile (Figure a), indicating that distinct behavioural repertoires are associated with distinct neurogenomic states, which differentiate not only sex but also male morphs. These results are consistent with previous studies that have already described this parallel between specific behavioural states and neurogenomic states at different timescales (reviewed in Zayed & Robinson, ; Harris & Hofmann, ; Cardoso, Teles, & Oliveira, ), and with previous reports of specific brain transcriptomic profiles among species with ARTs for alternative male morphs, particularly in teleost fishes (Aubin‐Horth et al., ; Fraser et al., ; Nugent et al., ; Partridge et al., ; Schunter et al., ; Stiver et al., ). For example, in bluegill sunfish ( Lepomis macrochirus ), the three male ARTs, encompassing two distinct life histories, presented distinct neurogenomic profiles, with sneaker males having the most divergent expression profile, while parental males were further discriminated in the analysis relatively to their reproductive state (i.e., spawning vs. nonspawning; Partridge et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous studies that have already described this parallel between specific behavioural states and neurogenomic states at different timescales (reviewed in Zayed & Robinson, ; Harris & Hofmann, ; Cardoso, Teles, & Oliveira, ), and with previous reports of specific brain transcriptomic profiles among species with ARTs for alternative male morphs, particularly in teleost fishes (Aubin‐Horth et al., ; Fraser et al., ; Nugent et al., ; Partridge et al., ; Schunter et al., ; Stiver et al., ). For example, in bluegill sunfish ( Lepomis macrochirus ), the three male ARTs, encompassing two distinct life histories, presented distinct neurogenomic profiles, with sneaker males having the most divergent expression profile, while parental males were further discriminated in the analysis relatively to their reproductive state (i.e., spawning vs. nonspawning; Partridge et al., ). In sailfin mollies ( Poecilia latipinna ), differentially expressed transcripts were also associated with each ART: in which small males and large males have fixed alternative tactics, always displaying sneaking and courtship behaviour, respectively, whereas intermediate males display courtship or sneaking behaviour depending on the male composition of their social environment (Fraser et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations